Four generations in a family with neurofibromatosis 1: precocious puberty and optic nerve tumor (OPT) - Gucev, Z; Krstevska Konstantinova, M; Tasic, V; Jancevska, Aleksandra; Kirovski, I; Pop Jordanova, Nada (Macedonian Academy of Sciences and Arts, 2010)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder with varied clinical manifestations. The proband is a 6-year-old boy with signs of precocious puberty. His penis was 10 cm, testicles 8 ml, pubic hair P2-3, and the genital skin was hyperpigmented. Multiple cafe au lait spots well above 5 mm were noticeable on his skin, as well as hard subcutaneous nodules, mostly on his trunk. His intelligence and hearing are normal. He has no history of seizures. Laboratory analysis showed: LH LH 1.4 mIU/ml, FSH 6.2 mIU/ml, testosterone 183 ng/ml. Bone age was 9 years. LHRH stimulation was characteristic of true precocious puberty (LH 9.8 mIU/ml and FSH 8.9 mIU/ml after 30 minutes). The MRI of the brain showed a tumor of the suprasellar region with compression of the pituitary stalk. At present the boy is 6 years old and has been treated with triptoreline acetate for 3 months. The volume of the testicles has decreased to 7 ml and a slight loss of pubic hair was noted. In addition, his mother and his grandfather exhibited dermal masses, and focal cutaneous and subcutaneous growths. The great-grand father had had the same cutaneous changes and died at the age of 75 from unrelated causes. It has already been well documented that NF is associated with an increased risk of malignancy and precocious puberty. Hence, we emphasize the need for a close and regular clinical follow-up of the OPT, puberty and patterns of growth.